Pengaruh Risiko Kredit, Risiko Likuiditas dan Risiko Operasional terhadap Kinerja Keuangan pada sebuah Perusahaan Perbankan yang tercatat di Bursa Efek Indonesia - Salsabila, Tri Sugiarti; Avionita, Venni (Jurnal Ilmiah Wahana Pendidikan, 2026)
Findings from studies of financial statement transactions may lead to revisions to bank workers' compensation plans. The findings of this investigation pose a challenge because the ROA ratio is utilised as a metric for evaluating financial success. You can evaluate different parts of operational risk, liquidity, and nonperforming loans with the help of the Book-to-Market (BOPO) ratio, Liquidity Coverage Ratio (LDR), and Nonperforming Loan (NPL) ratio, respectively. Secondary data is collected from various sources and organised using documentation processes for the purpose of research. The research's independent variable has a negative and insignificant effect on financial performance ratio (ROA), liquidity risk, and credit risk, but a positive and substantial effect on operational risk. performs unremarkably in relation to the financial results reported on the Indonesia Stock Exchange for the years 2018–2022.